RYEGRASS AND TALL FESCUE RESPONSES TO INOCULATION WITH Azospirillum amazonense AND Acaulospora scrobiculata - Alberton, Odair; Aguiar, Dione; Lermen, Caroline; Santos, Julio Cesar Pires; Filho, Osmar Klauberg (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2014)
In the Southern Brazilian Plateau, farmers try to compensate the lack of forage from native grasslands cultivatinggramineae such as ryegrass (Lolium multiflorum Lam.) and tall fescue (Festuca arundinacea). However, soil fertilityoften limits the productivity of these pastures. In this study, the authors investigated the effects of inoculating diazotrophicbacteria Azospirillum amazonense S22 and arbuscular mycorrhizal fungi (AMF) Acaulospora scrobiculata SCR855 on thegrowth and nutrient uptake of ryegrass and tall fescue. Both AMF and Azospirilum did not increase the dry weight and thenutrient concentration of ryegrass. However, Azospirillum inoculation promoted the growth of tall fescue. Mycorrhizal colonizationwas not affected by AMF inoculation, but it was increased by Azospirillum inoculation.